Inteligência emocional e liderança transformacional: um estudo psicossociológico - Lima, Erika Marques de Almeida (2023)
Emotional intelligence (EI) is conceptualized as the ability that individuals have to recognize and control their own emotions, as well as the awareness and sensitivity towards the emotions of others. Therefore, EI has been associated with the concept of leadership, which is now seen as a competence of a leader to guide, benefit the direction, engagement, and motivation of a group of people. In this context, this thesis aimed to study the constructs of emotional intelligence and transformational leadership anchored in the Theory of Social Representations (TSR), as this theoretical/methodological framework allows accessing the network of meanings and significances shared by a group of belonging, as well as studying them through theoretical and historical concepts. Structurally, this thesis was developed in two parts: the first part referring to the theoretical foundations and the second part to the empirical studies. The study entitled "The connections between Emotional Intelligence and Transformational Leadership: a systematic review" aimed to conduct a systematic review on the interconnection between emotional intelligence and transformational leadership. Searches were conducted for articles indexed in the Scielo and MEDLINE/Pubmed databases, published in the last 10 years (2012-2022), using the descriptors "transformational leadership" and "emotional intelligence," with the boolean operator AND to combine the terms. In the end, 6 articles were selected, their data described, and their abstracts analyzed through Hierarchical Descendant Classification, processed by the Alceste software. After data processing with Alceste, three thematic classes emerged, which were named: (i) "Types of leadership and emotional intelligence in the context of education," (ii) "Transformational leadership as a mediating factor for increased team effectiveness," and (iii) "The leader's emotional intelligence as a significant factor for employee performance at work." The scarcity of scientific productions on these topics in different continents and realities was also observed in the researched literature, as well as the need for the application of studies in the Brazilian context. The second article was an empirical study titled "Emotional intelligence and its relation to the concept of transformational leadership: a psychosociological study." This study aimed to examine the constructs of emotional intelligence and transformational leadership based on the theoretical framework of Social Representations. Fifty participants, aged 18 to 55 years (M=35.47), from a higher education institution in the state of Paraíba, Brazil, took part in the study. The instruments used included a sociodemographic questionnaire and the Free Association Word Technique. The textual production was processed using the ALCESTE software and analyzed using Hierarchical Descendant Classification, while the sociodemographic data were analyzed using SPSS (version 21). From the results of processing the interactions of social actors, three thematic classes emerged: (i) Concept of transformational leadership, (ii) conception of emotional intelligence, and (iii) leader's contributions to the team. The interlocutors' statements presented a profile of a participative leader, intervening to support their subordinates, expanding the studied concepts for the better personal and professional development of each individual involved. Being able to deal with one's own emotions and the emotions of others becomes a necessary condition, not only for the leader but also for everyone involved in relationships, whether in personal or professional spheres. The third study focused on the "Relationship between Emotional Intelligence and Transformational Leadership: a contribution to academic management." A total of 132 professionals participated in the study, distributed among teachers (69.7%), administrative staff (9.1%), department heads (18.2%), and teacher and technician roles (3.0%). They responded to three instruments: the Schutte Emotional Intelligence Scale (EIES) and the Transformational Leadership Questionnaire, both adapted for the Brazilian context, and a sociodemographic questionnaire. The majority were female (72.7%), ranging in age from 18 to 65 years, with the following distribution: 36 to 45 years (36.4%), 46 to 55 years (33.3%), 56 to 65 years (15.2%), 26 to 35 years (12.1%), and 18 to 25 years (3.0%). Furthermore, 97% reported having a postgraduate degree, with length of institutional experience ranging from 1 to 20 years. The results indicated an average score of 101.5 (SD ± 18.37) for emotional intelligence, indicating a mild level. For leadership styles, the transactional and transformational factors had average scores of 39.2 (SD ± 18.37) and 149.6 (SD ± 8.23), respectively, also indicating a mild level. A correlation between the transformational leadership and emotional intelligence constructs was also observed. It can be concluded that individuals with the ability to manage their own emotions are more likely to demonstrate empathy, sensitivity to the needs of others, as well as the ability to cope with the stress and pressure associated with higher education, maintaining calmness and acting assertively, thereby promoting satisfactory teaching and learning processes.